2020
DOI: 10.1177/0095327x20951435
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Experience? Innovative and Authoritative Leadership Values Among Danish Army Cadets

Abstract: Traditionally, the military is seen as an unequivocally authoritarian organization. With survey data collected at the Royal Danish Military Academy, this study shows that that is a qualified truth. Thus, cadets enrolled directly from the noncommissioned officer corps—those most acquainted with the norms of the armed forces—do not weigh authoritarian leadership values over nonauthoritarian ones. Instead, their view reflects that for the experienced leader, the context, and not overt ideals, enables them to choo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…More recent studies have highlighted the importance of other motivational aspects in the wars in Iraq and Afghanistan, among them abstract knowledge or self-realisation (Wong, Kolditz, Millen & Potter, 2003;Braender, 2016). And studies examining Moskos's I/O model have shown that instead of completely abandoning the institutional elements, the professional soldier is better described as a "pragmatic professional," driven both by his or her calling and by other motives (Segal, 1986;Woodruff, Kelty & Segal, 2006), and that the hallmark of the contemporary officer is his or her ability to shift between different leadership domains (Braender & Holsting, 2020).…”
Section: From Institution To Occupationmentioning
confidence: 99%
“…More recent studies have highlighted the importance of other motivational aspects in the wars in Iraq and Afghanistan, among them abstract knowledge or self-realisation (Wong, Kolditz, Millen & Potter, 2003;Braender, 2016). And studies examining Moskos's I/O model have shown that instead of completely abandoning the institutional elements, the professional soldier is better described as a "pragmatic professional," driven both by his or her calling and by other motives (Segal, 1986;Woodruff, Kelty & Segal, 2006), and that the hallmark of the contemporary officer is his or her ability to shift between different leadership domains (Braender & Holsting, 2020).…”
Section: From Institution To Occupationmentioning
confidence: 99%